Manajemen Kinerja Digital - Husnul Hotimah; Dwi Ambarwati; Mufarrohah Mufarrohah; Anasul Muttaqin; Mochammad Isa Anshori (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
In the current era of digitalization and globalization, information and communication technology has become an integral part of human life. The rapidly growing use of technology has also influenced almost all aspects of life, including the world of work. Technology has made work easier, increased productivity, and opened up new opportunities for companies to develop faster. Information and communication technology has now become an important factor in changing the way companies operate. Companies that are successful in facing technological changes and can utilize them effectively will have a competitive advantage in the market. Therefore, Human Resource Management (HRM) has experienced many changes since the start of the digital era. The digital era has had a significant impact on the way companies recruit, train and motivate their employees. In the digital era, companies not only need to understand technology, but also need to understand how technology can help in their human resource management.